2019
DOI: 10.1021/acsami.9b05999
|View full text |Cite
|
Sign up to set email alerts
|

Construction of CNA35 Collagen-Targeted Phase-Changeable Nanoagents for Low-Intensity Focused Ultrasound-Triggered Ultrasound Molecular Imaging of Myocardial Fibrosis in Rabbits

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
(61 reference statements)
1
19
0
Order By: Relevance
“…Zhou et al . designed an US-based multifunctional CNA35-labeled perfluoropentane nanoparticles (CNA35-PFP NPs) and injected them intravenously into a rabbit model of MI ( Zhou et al, 2019 ). It was found that CNA35-PFP NPs can effectively cross the interstitial space of endothelial cells and adhere to the surface of fibroblasts.…”
Section: Nanomaterials-mediated Diagnosis Strategies For MImentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al . designed an US-based multifunctional CNA35-labeled perfluoropentane nanoparticles (CNA35-PFP NPs) and injected them intravenously into a rabbit model of MI ( Zhou et al, 2019 ). It was found that CNA35-PFP NPs can effectively cross the interstitial space of endothelial cells and adhere to the surface of fibroblasts.…”
Section: Nanomaterials-mediated Diagnosis Strategies For MImentioning
confidence: 99%
“…Combining the unique advantages of US imaging with nanomaterials and attaching specific molecular markers to the surface of nano materials enables these nano scale contrast agents to target MI-specific antigens or antibodies. Zhou et al designed an US-based multifunctional CNA35-labeled perfluoropentane nanoparticles (CNA35-PFP NPs) and injected them intravenously into a rabbit model of MI (Zhou et al, 2019). It was found that CNA35-PFP NPs can effectively cross the interstitial space of endothelial cells and adhere to the surface of fibroblasts.…”
Section: Nanomaterials-enhanced Cardiac Imagingmentioning
confidence: 99%
“…Apart from EP‐3533, gold (Au) nanoparticles have also been explored for targeted imaging of collagen. Zhou et al [ 73 ] constructed CNA35‐labeled perfluoropentane nanoparticles. These nanoparticles could specifically target fibroblasts and collagen.…”
Section: Nanomedicines Targeting Extracellular Matrixmentioning
confidence: 99%
“…Anaplastic thyroid carcinoma (ATC) is one of the most malignant carcinomas, though it is comparatively rare, characterized by fast proliferation, neck invasion, and remote metastasis (Zhu et al, 2018;Zhong et al, 2019;Zhou et al, 2019;. The severe prognosis that accompanies ATC is due to the rapid progression of tumors before diagnosis.…”
Section: Introductionmentioning
confidence: 99%